2012
DOI: 10.1097/mpg.0b013e3182645c54
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Against Deamidated Gliadin Peptides and Tissue Transglutaminase for Diagnosis of Pediatric Celiac Disease

Abstract: For diagnosing CD, tTG is superior to DGP, even in children younger than 2 years. Combining tTG and DGP does not provide a better tradeoff between number of missed cases of CD, number of unnecessary duodenal biopsies, and cost than tTG alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 17 publications
5
50
1
Order By: Relevance
“…However, a recent study [12 & ] showed that there were two subgroups of patients with IgAD (switched memory B cells percentage: 0. 34 ] also determined major lymphocyte subpopulations and B-lymphocyte subsets in patients with IgAD and confirmed the reduction in terminally differentiated B-lymphocyte subsets, similar to what has previously been found in patients with CVID, although less pronounced than in the latter.…”
Section: Updatesupporting
confidence: 79%
“…However, a recent study [12 & ] showed that there were two subgroups of patients with IgAD (switched memory B cells percentage: 0. 34 ] also determined major lymphocyte subpopulations and B-lymphocyte subsets in patients with IgAD and confirmed the reduction in terminally differentiated B-lymphocyte subsets, similar to what has previously been found in patients with CVID, although less pronounced than in the latter.…”
Section: Updatesupporting
confidence: 79%
“…In fact, our findings are in accord with a recent Swedish study evaluating the use of tTG-IgA in clinical practice, which found that among 26 180 children screened for CD primarily by general practitioners or pediatricians (and presumably because of symptoms or conditions suggestive of CD), only 1.3% were diagnosed with CD. 23 A systematic overview of diagnostic testing for CD among adult patients with abdominal symptoms within primary care also revealed that gastrointestinal symptoms alone were not sufficiently accurate for predicting CD. 24 Case-finding by asking for CD-associated conditions also revealed poordiagnostic performance in this population, and the prevalence of undiagnosed CD among children with these conditions was lower than the CD prevalence usually described for these groups.…”
Section: Figurementioning
confidence: 99%
“…IgG t-TGA can be used in cases of IgA-deficiency (Husby 2012). Antibodies towards tissue tranglutaminase have higher sensitivity in comparison to those towards endomysium (Giersiepen 2012, Olén 2012. Table 1.…”
Section: Diagnosis Serologymentioning
confidence: 99%
“…less than two years of age, antibodies against DGP appear before antibodies to tissue transglutaminase (t-TGA) and can be considered a useful test when the other tests are negative (Husby 2012). In cases of patients with IgA-deficiency, IgG antibodies to DGP can be tested as a complement to antibodies to t-TGA (Olén 2012). The sensitivity and specificity of IgA and IgG towards DGP varies (Giersiepen 2012) (Table 1).…”
Section: Diagnosis Serologymentioning
confidence: 99%